Evaluation of IGF1 serum levels in malignant melanoma and healthy subjects - Kucera, Radek; Treskova, Inka; Vrzalova, Jindra; Svobodova, Sarka; Topolcan, Ondrej; Fuchsova, Radka; Rousarova, Milena; Treska, Vladislav; Kydlicek, Tomas (Anticancer research, 2014)
BACKGROUND/AIM: There were two aims in the present study. The first was to evaluate the usefulness of insulin-like growth factor 1 (IGF1) for melanoma detection. The second was to correlate changes of serum levels of IGF1 with the Breslow score and sentinel node metastasis positivity. PATIENTS AND METHODS: We examined a group of 216 cases, 77 patients with melanomas and 139 healthy probands. We determined the serum IGF1 levels of each patient using an IRMA radioisotope IGF1 assay kit. Serum samples were collected prior to surgery or any other form of treatment. All melanoma diagnoses were histologically verified. RESULTS AND DISCUSSION: Based on the statistical evaluation between the melanoma group and group of healthy individuals, we observed statistically significant differences in IGF1 serum levels. The median IGF1 levels in the melanoma group was 154.1 ng/ml compared to 111.2 ng/ml in the group of healthy individuals (p=0.0036). The changes of the IGF1 levels related to the Breslow score categories were statistically significant (p=0.0027). Lastly, we compared the results between the positive and negative metastatic affection of the sentinel nodes. The median IGF1 levels in the negative group was 173.5 ng/ml compared to 205.8 ng/ml in the positive group. This difference was statistically significant (p=0.0407). CONCLUSION: Serum levels of IGF1 were significantly higher in patients diagnosed with melanoma compared to the healthy control group. The changes of the IGF1 levels related to the Breslow score categories were statistically significant. Serum levels of IGF1 were significantly higher in the group with the positive metastatic affection of the sentinel nodes than in negative patients.
Keywords: dospělí; Insulin-Like Growth Factor I; dítě; biologické markery; Biomarkers; Lymphatic Metastasis; lymfatické metastázy; Adult; mladý dospělý; Adolescent; IGF1; lidé; studie případů a kontrol; Aged, 80 and over; prognóza; biopsie sentinelové lymfatické uzliny; Breslow score; insulinu podobný růstový faktor I; melanom; Case-Control Studies; Aged; Young Adult; sentinel node metastasis; Prognosis; Sentinel Lymph Node Biopsy; lidé středního věku; Child; senioři nad 80 let; senioři; Middle Aged; mladiství; Melanoma; Humans